The Effects of Localisation Decisions on New Product Superiority and Performance: Empirical Research on Consumer-Goods Subsidiaries - Jusmaliani, Firmanzah (UI Scholars Hub, 2021)
New products, while essential, are risky and expensive for subsidiaries. The main objective of this research is to determine success factors for new product launch (NPL) by subsidiaries operating in developing countries. It is argued that localisation of NPL decisions contributes positively to new product superiority and commercial performance, with partial least squares used to test the hypothesis. The results show that localisation of innovation decisions increases localisation of branding and commercialisation decisions in the local market. However, localisation of commercialisation decisions positively influences new product superiority, while localisation of innovation decisions reduces this superiority. Finally, hypothesis testing reveals that localisation of commercial decisions and new product superiority both increase the commercial performance of new products in the local market.